MODEL PENDEKATAN TERAPI CLIENT-CENTERED SEBAGAI PENDAMPINGAN PASTORAL KONSELING BAGI RESDIVIS DI LAPAS KELAS III AMURANG - Ester R.J. Manginsihi; Meily Meiny Wagiu; Novita Pardamean Sianturi (PT. Giat Konseling Nusantara, 2024)
Some of the objectives of this study include finding out how the pastoral counseling program for recidivists in prisons is, finding out how the challenges and efforts are in handling pastoral counseling for recidivists in prisons through a client-centered approach, and finding out how effective the client-centered approach is in supporting rehabilitation for recidivists in Amurang prison. Based on the results of the client-centered therapy approach study for recidivists in Amurang prison, it was found that the client-centered approach has proven effective in supporting rehabilitation for recidivists in Amurang prison. This can be seen from the increase in self-confidence, self-acceptance, reduction of stigma, and increased self-awareness of recidivists. In this study, the researcher used qualitative research using a case study approach. This method is carried out with the aim of digging up in-depth information on the research subjects through observation, interviews, as well as pastoral counseling.